APOLOGETIKA DIALOGIS - Soleman Kawangmani (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2020)
Paguyuban Ngesti Tunggal (PANGESTU) is proliferating. PANGESTU claims that all religions are the same and are the essence of all formal religions' teachings. The postmodern context that upholds pluralism and truth relativism is challenging in proclaiming the Good News, especially for PANGESTU followers. Therefore, a new way of applying apologetics is needed to reach postmoderns. This study aimed to find the application of apologetics as a conversation model for the Good News in the PANGESTU mystical context. This study uses a qualitative approach. The method used is biblical hermeneutics and literature study. The researcher found "Dialogical Apologetics Olah Rasa" as a conversation model for Good News in the context of PANGESTU mysticism, which consists of 4 stages, namely: Stage I, Building dialogical relationships with PANGESTU followers; Stage II, Dialogical Apologetics Olah Rasa as the pre-news of the Good News; Stage III, Proclamation of the Good News; Stage IV, Dialogical Apologetics Olah Rasa as a Discipleship.